The common pathophysiology underlying the metabolic syndrome, schizophrenia and depression. A review - Rudá Kučerová, Jana; Babinská, Zuzana; Horská, Kateřina; Kotolová, Hana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND: There is a growing interest in metabolic alterations in patients with psychiatric disorders due to their increased risk for metabolic syndrome (MetS) development. Inflammation is known to underlie the pathophysiology of schizophrenia and depression as well as MetS. Vulnerability factors for schizophrenia/depression and MetS hence appear to be shared. METHODS AND RESULTS: Based on a Web of Science search, this review examines current evidence for MetS pathophysiology involving dysregulation of adipose tissue signaling - adipokines and pro-inflammatory cytokine, both also known to be aberrant in schizophrenia/depression. Further, gender differences in the incidence and course of schizophrenia/depression were reported. The disturbances linked to the MetS are also described. Therefore, this review further maps the gender differences in the psychiatric-metabolic comorbidities. CONCLUSION: There is evidence supporting a pathological predisposition to MetS in both schizophrenia and depression in both humans and animal models. This predisposition is dramatically enhanced by antipsychotic medication. Further, there are gender differences from clinical findings suggesting women with schizophrenia/depression are more vulnerable to MetS development. This has not yet been assessed in animal studies. We suggest further validation of existing schizophrenia and depression animal models for the assessment of metabolic disturbances to provide tools for developing new antipsychotics and antidepressants with "metabolically inert" profile or improving the metabolic status in schizophrenic/depressed patients.
Keywords: Cytokines; Sex Characteristics; Resistin; resistin; Schizophrenia; Disease Models, Animal; zvířata; cytokiny; Depressive Disorder; zánět; lidé; Animals; modely nemocí na zvířatech; Inflammation; metabolický syndrom; Female; Male; ženské pohlaví; pohlavní dimorfismus; Humans; depresivní poruchy; mužské pohlaví; Metabolic Syndrome; schizofrenie